Excavations at Schöningen and paradigm shifts in human evolution. Issue 89 (December 2015) - Conard, Nicholas J.; Serangeli, Jordi; Böhner, Utz; Starkovich, Britt M.; Miller, Christopher E.; Urban, Brigitte; Van Kolfschoten, Thijs
Abstract: The exceptional preservation at Schöningen together with a mixture of perseverance, hard work, and sheer luck led to the recovery of unique finds in an exceptional context. The 1995 discovery of numerous wooden artifacts, most notably at least 10 carefully made spears together with the skeletons of at least 20 to 25 butchered horses, brought the debate about hunting versus scavenging among late archaic hominins and analogous arguments about the purportedly primitive behavior of Homo heidelbergensis and Neanderthals to an end. Work under H. Thieme's lead from 1992 to 2008 and results from the current team since 2008 demonstrate that late H. heidelbergensis or early Neanderthals used sophisticated artifacts made from floral and faunal materials, in addition to lithic artifacts more typically recovered at Lower Paleolithic sites. The finds from the famous Horse Butchery Site and two dozen other archaeological horizons from the edges of the open-cast mine at Schöningen provide many new insights into the technology and behavioral patterns of hominins about 300 ka BP during MIS 9 on the Northern European Plain. An analysis of the finds from Schöningen and their contexts shows that the inhabitants of the site were skilled hunters at the top of the food chain and exhibited a high level of planning depth. These hominins had command of effective means of communication about the here and now, and the past and the future, that allowed them to repeatedly execute well-coordinated and successful group activities that likely culminated in a division of labor and social and economic patterns radically different from those of all non-human primates. The unique preservation and high quality excavations have led to a major paradigm shift or "Schöningen Effect" that changed our views of human evolution during the late Lower Paleolithic. In this respect, we can view the behaviors documented at Schöningen as a plausible baseline for the behavioral sophistication of archaic hominins of the late Middle Pleistocene and subsequent periods.